Technological unemployment revisited: Automation in a search and matching framework - Dario Cords; Klaus Prettner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
Will low-skilled workers be replaced by automation? To answer this question, we set up a search and matching model that features two skill types of workers and includes automation capital as an additional production factor. Automation capital is a perfect substitute for low-skilled workers and an imperfect substitute for high-skilled workers. Using this type of model, we show that the accumulation of automation capital decreases the labor market tightness in the low-skilled labor market and increases the labor market tightness in the high-skilled labor market. This leads to a rising unemployment rate of low-skilled workers and a falling unemployment rate of high-skilled workers. In addition, automation leads to falling wages of low-skilled workers and rising wages of high-skilled workers.
urn:nbn:de:bsz:100-opus-15305
Keywords: C78; J63; J64; O33; 330; unemployment; automation; search and matching model; technological progress; inequality; skill premium